A Review of Supply Chain Risk Management in Agribusiness Industry - Widiyanesti, Sri; Fernando, Yudi (IGI Global USA, 2018)
Supply chain of agricultural commodities becomes a major concern of Indonesian scholars and practitioners. Many companies engaged in this industry unable to survive in the market. This is contrary to the natural conditions of Indonesia with abundant natural resources and plenty of commodity producers. Problems often arise in the field of supply chain risk which link to commodities in Indonesia, among others: price fluctuation, the scarcity of the commodity, supply and demand are not balanced, distribution and production costs are expensive, raw material commodities that are imported, and natural disasters. Companies which engaged in agricultural business have high risk of survival and not even grow. To overcome this challenges the this chapter intend to review supply chain management concept by look at risk consideration may arise in the business uncertainties. The lack of studies to investigate the risk factors in agribusiness makes this study contribute to the supply chain literature.